A porous nickel cyclotetraphosphate nanosheet as a new acid-stable electrocatalyst for efficient hydrogen evolution. Issue 21 (23rd May 2018) - Liu, Xiong; Wen, Bo; Guo, Ruiting; Meng, Jiashen; Liu, Ziang; Yang, Wei; Niu, Chaojiang; Li, Qi; Mai, Liqiang
Abstract : The porous nickel cyclotetraphosphate nanosheet arrays exhibit both high HER activity and catalytic stability in acid. Abstract : The stability of non-precious metal-based electrocatalysts for the acidic hydrogen evolution reaction (HER) is of great importance. Here, we have used nickel cyclotetraphosphate (Ni2 P4 O12 ) nanosheet arrays as a HER electrocatalyst for the first time. The Ni2 P4 O12 arrays were obtained through a facile low-temperature phosphorylation process and possess superior HER catalytic activities and stability in acid. The Ni2 P4 O12 delivers a small overpotential of 131.8 mV at −10 mA cm −2 and a low Tafel slope of 47.8 mV dec −1 in 0.5 M H2 SO4, comparable to most of the non-precious metal-based catalysts. Importantly, the Ni2 P4 O12 shows a negligible potential change (6.5 mV) over 80 000 s continuous testing in acid. The remarkable catalytic performances of Ni2 P4 O12 are mainly attributed to the inductive effect of P4 O12 4− and its polymer-like structure, promoting it as a potential acid-stable HER electrocatalyst.